Characterization of piezoelectric properties of In2Se3 and GaInS3 using piezo force microscope - Yao, Yuan (Nanyang Technological University, 2024)
The advent of two-dimensional materials, including graphene, phosphorene, and molybdenum disulfide, etc, has propelled technological progress in new electronic materials, enabling the realization of increasingly sophisticated advancements in novel electronic devices. The piezoelectric effect, a fundamental phenomenon wherein a mechanical strain induces electric polarization, holds substantial promise for various applications in the realm of nanoelectronics and sensors. Some 2D materials exhibit pronounced piezoelectric coefficients that make them promising candidates for energy harvesting, sensing, and actuation technologies. In the realms of energy harvesting and mechanical sensing, the piezoelectric properties of 2D piezoelectric materials offer opportunities to convert mechanical vibrations and strains into electrical energy and signals, potentially revolutionizing self-powered sensing systems. Moreover, the sensitivity of 2D material-based piezoelectric sensors makes them suitable for detecting minute forces, pressures, and biochemical interactions in various applications, including healthcare and environmental monitoring. The piezoelectric properties of GaInS3 and In2Se3, two distinct two-dimension (2D) materials, have been studied in this thesis through iterative Piezoresponse Force Microscopy (PFM) and Atomic Force Microscopy (AFM) scanning experiments, along with Second Harmonic Generation (SHG) response testing. This thesis focuses on the observations of the piezoelectric responses and the analysis of the associated piezoelectric coefficients for the aforementioned two materials.